2022
DOI: 10.3390/foods11081108
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Validation of a DNA Metabarcoding Assay for Mammalian and Poultry Species to Detect Food Adulteration

Abstract: Meat species authentication in food is most commonly based on the detection of genetic variations. Official food control laboratories frequently apply single and multiplex real-time polymerase chain reaction (PCR) assays and/or DNA arrays. However, in the near future, DNA metabarcoding, the generation of PCR products for DNA barcodes, followed by massively parallel sequencing by next generation sequencing (NGS) technologies, could be an attractive alternative. DNA metabarcoding is superior to well-established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Several NGS-based or metabarcoding methods also exist in the field of meat analysis ( Ballin et al, 2009 ). A metabarcoding method for the identification of mammalian and poultry species in food ( Dobrovolny et al, 2019 ) has already been tested for routine analysis ( Preckel et al, 2021 ) and has been validated in an interlaboratory ring trial in order to harmonize analytical methods for food authentication ( Dobrovolny et al, 2022 ). Based on the data of this ring trial, the authors suggested a threshold of 0.5 % to reliably assess the presence of a species in a food sample ( Dobrovolny et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several NGS-based or metabarcoding methods also exist in the field of meat analysis ( Ballin et al, 2009 ). A metabarcoding method for the identification of mammalian and poultry species in food ( Dobrovolny et al, 2019 ) has already been tested for routine analysis ( Preckel et al, 2021 ) and has been validated in an interlaboratory ring trial in order to harmonize analytical methods for food authentication ( Dobrovolny et al, 2022 ). Based on the data of this ring trial, the authors suggested a threshold of 0.5 % to reliably assess the presence of a species in a food sample ( Dobrovolny et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding quantification, in meat analysis, the determination of the meat content of species is associated with similar problems, such as the use of mtDNA, processing grade and DNA extractability which impact on the quantitative results. Therefore, results are rather considered as rough estimates for the compositions of mixed species in food products ( Cottenet et al, 2020 , Dobrovolny et al, 2022 , Preckel et al, 2021 ). Factors contributing to a bias of PCR-based methods can result from various sources in the analytical process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, meat authentication is an important concern to protect consumers from illegal and unwanted ingredients. Accordingly, three papers dealing with meat authenticity, origin, and detection of meat adulteration using OMICs methods were published [ 15 , 16 , 17 ]. Cai et al [ 15 ] proposed a simple and reliable single-tube septuple PCR assay based on mitochondrial DNA to simultaneously recognize seven meat species from pig, beef, sheep, chicken, turkey, goose, and duck.…”
mentioning
confidence: 99%
“…Furthermore, the authors validated the method in terms of sensitivity, specificity, robustness, and low costs for broad application to detect the origin of meat in foodstuffs with suspected adulteration. Another interesting study by Dobrovolny et al [ 16 ] consisted of a collaborative work among 15 laboratories (inter-laboratory ring trial) that aimed to harmonize an analytical method based on DNA metabarcoding assay to detect adulteration from poultry and mammalian species. In this European study, each research team received and analyzed 16 anonymously labeled samples (8 samples, 2 subsamples each) containing six mixtures of DNA extract, one DNA extract from a model sausage, and another from maize, considered in this trial as a negative control.…”
mentioning
confidence: 99%